Loving Neighbor as Self: Translating the Study Abroad Experience into Intercultural Friendships on the Home Campus - Pengelly, Kelly A. (Journal of International Students, 2018)
Universities focus significant attention on internationalization to prepare empathyglobally minded graduates by engaging students in study abroad programs and expanding international student enrollment. However, scholarship has not yet considered the role returned study abroad students play in meeting friendship needs of international students. This research aimed to determine if such experiences impact friendships between participants and internationals. Four basic themes emerged: isolated application of intercultural competencies, differences in empathy experiences, friendships between study abroad and international students, and institutional contributions. Key findings revealed institutions do not teach study abroad students to utilize their experience in fostering empathetic friendships withinternational students and should consider how the experience can more effectively impact intercultural friendships rather than focusing solely on domestic students’ reverse culture shock.